Revisiting heidegger on schematism - Salman Sakızlı, Selda (My University, 2020)
Although it is very short, the section on Schematism in the Critique of Pure Reason is one of the most significant sections in the book. In a note dated 1797 Kant admits that that it is one of the most important and the most difficult sections in the Critique.' The basic claims of schematism can be observed in Kant’s Inaugural Dissertation dated 1770, although most of the theses of the Dissertation have changed, the claims and the importance concerning the schemas remained almost the same.1 2 As a matter of fact, even though Kant made considerable changes on the sections about the roles and functions of the faculty of imagination in the second edition of the Critique, such as the Deduction section, Schematism remains almost untouched. 1 Reflexionen, 6359, 18:686, pp. 393-394 2 See Karin De Boer, Kant’s Account of Sensible Concepts in the Inagural Dissertation and the Critique of Pure Reason. Natur und Freiheit. Akten des XII. Intemationalen Kant-Kongresses, Ed. Violetta Waibel, Margit Ruffing, David Wagner, De Gruyter: Berlin, https://doi.org/10.1515/9783110467888-021, 2018, p. 1015-1022 2 CPR, A138/ BlT1 4 See Martin Heidegger, Kant and the Problem of Metaphysics, Trans. Richard Taft. Indiana University Press, Indianapolis, 1997, and Phenomenological Interpretation of the Critique of Pure Reason, Trans. Parvis Emad and Kenneth Maly, Indiana University Press, Indianapolis, 2018 s CPR, A140/ B179 The main argument in schematism is subsuming the object (Gegenstand) under a concept and in that respect providing homogeneity between the appearances and concepts. This need appears as a result of Kant’s separation between the sensibility and the understanding and the clear distinction of the two concerning their roles and functions. As they have to stand apart there is the need to connect them in order to provide cognition. Kant states “Now it is clear that there must be a third thing, which must stand in homogeneity with the category on the one hand and the appearance on the other, and makes possible the application of the former to the latter.”3 Kant calls this “mediating” representation, which is both intellectual and sensible, a transcendental schema, which is always the product of the faculty of imagination. Martin Heidegger, who interprets Kant in phenomenological tradition and stresses the importance of imagination in Kantian philosophy, also focuses on the Schematism section as one of the important parts of his interpretation.4 Heidegger suggests a new word, “schemaimage” though he is aware of the fact that image is not a schema, but thus he approximates schema with image and excludes non-ocular experience. In this paper, I will criticize Heidegger’s interpretation of schematism since Kant is very clear about the difference between an image and a schema which are both the products of the imagination.5 But image is always the representation of a particular thing; on the contrary, schema is neither a singular intuition nor a concept.